The Taxation of Risky Assets - Bulow, Jeremy I.; Summers, Lawrence H. (Journal of Political Economy, 1984)
This paper reconsiders the effects of taxation on risky assets, recognizing the importance of variations in asset prices. We show that earlier analyses which assumed that depreciation rates are constant and that the future price of capital goods is known with certainty are very misleading, as guides to the effects of corporate taxes. We then examine the concept of economic depreciation in a risky environment, and show that depreciation allowances, if set ex-ante, should be adjusted to take account of future asset price risk. Some empirical calculations suggest that these adjustments are large, and have important implications for the burdens of, and non-neutralities in, the corporate income tax.